Oral mucosal lesions in the mouth as first sign of dermatological diseases and disorders - Karthikeyini, Harepriya Meganathan; Shunmugavelu, Karthik; Dhinakaran, Evangeline Cynthia (German Medical Science GMS Publishing House, 2024)
Oral mucosal lesions manifest as a first sign of immune-mediated disorders. Lichen planus, pemphigus and pemphigoid are the most frequent immunologically mediated mucocutaneous diseases with oral involvement. Oral lesions are initially detected by dental health practitioners. Early detection can help in appropriate treatment and better quality of life. Based on an analysis of 6,300 medical records from the period 1997 to 2018, 105 (1.66%) were attributable to these immunologically mediated diseases, of which 86 (1.36%) were due to lichen planus, 4 (0.06%) to pemphigus and 15 (0.23%) to pemphigoid.